Inhibition of calcium/calmodulin-dependent protein kinase IV in arthritis: dual effect on Th17 cell activation and osteoclastogenesis. (4th July 2022) - Koga, Tomohiro; Umeda, Masataka; Yoshida, Nobuya; Satyam, Abhigyan; Jha, Meenakshi; Scherlinger, Marc; Bhargava, Rhea; Tsokos, Maria G; Sato, Tomohito; Furukawa, Kaori; Endo, Yushiro; Fukui, Shoichi; et al.
Abstract: Objective: To investigate the role of calcium/calmodulin-dependent protein kinase IV (CaMK4) in the development of joint injury in a mouse model of arthritis and patients with RA. Methods: Camk4 -deficient, Camk4 flox/flox Lck -Cre, and mice treated with CaMK4 inhibitor KN-93 or KN-93 encapsulated in nanoparticles tagged with CD4 or CD8 antibodies were subjected to collagen-induced arthritis (CIA). Inflammatory cytokine levels, humoral immune response, synovitis, and T-cell activation were recorded. CAMK4 gene expression was measured in CD4 + T cells from healthy participants and patients with active RA. Micro-CT and histology were used to assess joint pathology. CD4 + and CD14 + cells in patients with RA were subjected to Th17 or osteoclast differentiation, respectively. Results: CaMK4-deficient mice subjected to CIA displayed improved clinical scores and decreased numbers of Th17 cells. KN-93 treatment significantly reduced joint destruction by decreasing the production of inflammatory cytokines. Furthermore, Camk4 flox/flox Lck - Cre mice and mice treated with KN93-loaded CD4 antibody-tagged nanoparticles developed fewer Th17 cells and less severe arthritis. CaMK4 inhibition mitigated IL-17 production by CD4 + cells in patients with RA. The number of in vitro differentiated osteoclasts from CD14 + cells in patients with RA was significantly decreased with CaMK4 inhibitors. Conclusion: Using global and CD4-cell-targeted pharmacologic approaches and conditionally deficient mice, we demonstrate that CaMK4 is important in the development of arthritis. Using ex vivo cell cultures from patients with RA, CaMK4 is important for both Th17 generation and osteoclastogenesis. We propose that CaMK4 inhibition represents a new approach to control the development of arthritis.